Nexus between digital tourism "hackathon", value co-creation, reward-based crowdfunding and destination competitiveness in post-pandemic tourism - Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Open innovation platforms are transforming global tourism by enhancing visitors experience, creating resilient destinations, mobilizing creativity and shared expertise across diverse stakeholders. The present research explores the impact of digital tourism hackathon, reward-based crowdfunding and value co-creation on destination competitiveness through an online survey of tourism industry professionals (N=479). Based on prominent theories (i.e., innovation diffusion theory, stakeholder theory and social exchange theory) and statistical estimations with partial least square structural equation modeling (PLS -SEM), the present study provides ground-breaking evidence that tourism value co-creation positively mediates the effects of digital tourism 'hackathon' and reward-based crowdfunding on destination competitiveness. In addition, the SEM-based findings also validate that destination competitiveness is significantly and positively influenced by digital tourism hackathon and reward-based crowdfunding. The practical implications include strategic insights for tourism policymakers and destination managers to leverage technology and innovation for sustainable tourism development. The present study highlights various approaches to foster collaboration and innovation, besides overcoming the challenges of implementing open innovation through governance frameworks and equitable partnerships for shared tourism benefits.
Keywords: 330; Digital tourism hackathon; reward-based crowdfunding; destinationcompetitiveness; value co-creation; innovation diffusion theory; stakeholder theory andsocial exchange theory; United Arab Emirates